Spatial synchrony of population dynamics: Empirical testing of mechanisms. Issue 8 (9th August 2019) - Zytynska, Sharon E.
Abstract: In Focus: Vindstad, O. P. L., Jepsen, J. U., Yoccoz, N. G., Bjørnstad, O. N., Mesquita, M. d. S., & Ims, R. A. (2019). Spatial synchrony in sub‐arctic geometrid moth outbreaks reflects dispersal in larval and adult life cycle stages. Journal of Animal Ecology, 88, 1134–1145.https://doi.org/10.1111/1365-2656.12959 . Spatial synchrony of population dynamics is a common phenomenon, but the understanding of underlying mechanisms is supported more by theoretical than empirical studies. Vindstad et al. (2019) use a 19‐year dataset on two moth species to disentangle the effects of different drivers of dispersal on the synchrony of populations. They show that geographic distance, species dispersal capabilities, a dispersal barrier and the prevailing wind direction are all factors that influence spatial synchrony. With current climate change and ongoing habitat fragmentation, understanding how dispersal influences spatial synchrony of population fluctuations, and the effect on population viability, is essential to predict future impacts on our ecosystems. Abstract : Understanding how dispersal influences spatial synchrony of population dynamics, and the effect on population viability, is essential to predict future impacts on our ecosystems.